Does the face show what the mind tells? A comparison between dynamic emotions obtained from facial expressions and Temporal Dominance of Emotions (TDE). (October 2020) - van Bommel, Roelien; Stieger, Markus; Visalli, Michel; de Wijk, Rene; Jager, Gerry
Highlights: Comparison between Temporal Dominance of Emotions (TDE) and FaceReader™ was performed. Multiple bite evaluations of yogurt with granola were done. Emotion profiles of food products did not change over the course of consumption. Emotion profiles obtained with TDE and FaceReader™ show little overlap. Abstract: Measuring food-evoked emotions dynamically during consumption can be done using explicit self-report methods such as Temporal Dominance of Emotions (TDE), and implicit methods such as recording facial expressions. It is not known whether or how dynamic explicit and implicit emotion measures correspond. This study investigated how explicit self-reported food-evoked emotions evaluated with TDE are related to implicit food-evoked emotions determined from facial expressions. Fifty-six participants evaluated six yogurts with granola pieces varying in size, hardness and concentration, using multiple bite assessment employing TDE for the first, third and fifth bite of consumption. Consumers were video recorded during each bite of consumption and facial expressions were analysed using FaceReader™. Happy, interested, disgusted and bored were similar descriptors measured explicitly and implicitly. Little overlap was observed regarding the type of emotion characterization by FaceReader™ and TDE. Products were mainly discriminated along the valence dimension (positive – negative), and directly reflected product discrimination in terms of liking. FaceReader™ further differentiated the least liked products from each other on arousal and negative facial expressions. Our results indicated little dynamics in food-evoked emotions within and between bites. Facial expressions seemed more dynamic within bites, while explicit food-evoked emotion responses seemed more dynamic between bites. We conclude that FaceReader™ intensities of emotions and dominance durations observed in TDE are not directly comparable and show little overlap. Moreover, food-evoked emotion responses were fairly stable from first to last bite and only very limited changes were observed using implicit and explicit emotions measures.